Efficacy of laser acupuncture for carpal tunnel syndrome: A study protocol for a prospective double-blind randomized controlled trial - Chen, Chuan-Chih (Medicine (Baltimore), 2019)
INTRODUCTION: Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy that causes hand discomfort and work disability. Since no satisfactory conventional treatments for mild to moderate CTS exist, we apply complementary alternative medicine (CAM) to this problem. Laser acupuncture (LA), a new, non-invasive therapy which uses low-level-laser therapy (LLLT) in acupuncture could help to manage CTS. However, only one small randomized, double-blind and crossover trial had been conducted, which is not enough to provide an evidence-based assessment of the effects of LA on CTS. OBJECTIVES: The aim of this study protocol is to investigate the efficacy of LA therapy on patients with mild to moderate CTS through sonography of the median nerve and offer clear parameters of LLLT. METHODS: This study protocol is a prospective double-blind randomized controlled trial. Forty subjects aged 20 to 80 years old and diagnosed as having mild to moderate CTS will be randomly assigned to the intervention group (real LA, 3-sessions a week for 2 weeks) and control group (sham LA, 3-sessions a week for 2 weeks). All subjects will be asked to wear night splints as the fundamental management approach. The laser parameters will include a wavelength of 808 nm, power output of 300 mW and power density of 300 mW/mm(2), with ten seconds of treatment for each acupuncture point (PC4, PC6, PC7, PC8, LI4, LI10, LI11, HT3, HT7, and LU10). Sham LA treatment will be applied without any laser power output. The primary outcome will be based the Boston Carpal Tunnel Syndrome Questionnaire and secondary outcomes included a visual analog scale, cross sectional area of median nerve by sonography and electrophysiological test before interventions and after 2, 4, 8, 12 weeks postintervention. TRIAL REGISTRATION: ClinicalTrials.gov (Identifier: NCT03580265).